Income distribution dynamics of economic systems an econophysical approach - Ribeiro, Marcelo Byrro 1960- (Cambridge University Press, 2020)
"The book deals with the empirical characterization and dynamics of income distribution and its related quantities from the epistemological and practical perspectives of contemporary physics. Part I discusses the methodological basis of econophysics, several distribution functions used to model the income data and presents empirical evidence supporting those distribution functions. Thomas Piketty's book on inequality is also partially reviewed. Part II discusses income and wealth distributions from the viewpoint of statistical physics, presenting a series of models of the income distribution characterization and dynamics. Part III deals with income distribution under the viewpoint that economic systems have circular flows. This dynamic approach is able to connect income classes to macroeconomic trade cycle theories. Issues like uncertainty, confidence, investment and stability are discussed and the Goodwin macroeconomic dynamics of growth with cycles is discussed in detail. Several other models based or inspired on this macrodynamics are presented and discussed"--